Behavioural variability and repeatability in adult zebrafish (Danio rerio) using the novel tank dive test - Johnson, Andréa L.; Hurd, Peter L.; Mathot, Kimberley J.; Hamilton, Trevor (My University, 2025)
Zebrafish (Danio rerio) are widely used in behavioural neuroscience as a model for studying anxiety-like and stress-related behaviours. However, substantial variability exists within and among individuals, influenced by factors such as sex, age, and environmental conditions, making the interpretation of anxiety-related behaviours challenging. Here we characterized longitudinal patterns of stability and variability in anxiety-like behaviours across individual adult zebrafish and assessed whether distinct behavioural profiles emerged over time. Using the novel tank dive test, we tracked anxiety-related behaviours in zebrafish across multiple time points over a 21-week period (90, 120, and 150 days post-fertilization). Behavioural metrics, including time spent in tank zones, swimming velocity, and immobility, were analyzed for age- and sex-related effects, repeatability, and group variation. Results indicated significant changes in anxiety-like behaviours with age, with fish spending more time in the upper zone and displaying increased swimming velocity over time. While no significant sex differences were observed in zone preference, males exhibited greater within-individual variation in time spent in the lower zone, while females demonstrated higher among-individual variation and repeatability over time. Furthermore, zebrafish were classified into high, medium, and low-anxiety groups based on cumulative behavioural scores, revealing stable individual differences in anxiety-like behaviours. These findings highlight the importance of considering age, sex and both intra- and inter-individual variation when interpreting zebrafish behaviour and provide a foundation for future research exploring selective breeding, anxiety level interactions, and pharmacological modulation of anxiety-related phenotypes.
Keywords: behavioural neuroscience; zebrafish (Danio rerio); anxiety-like behaviours; novel tank dive test